Smart contract development and blockchain technology development - Quak, Justina Lin Ying (Nanyang Technological University, 2023)
This report aims to address the issue of medical certificate forgery by providing a tamper-proof way of issuing medical certificates using blockchain technology. The report provides background information on the issue of medical certificate forgery, its current pain points, and the local context. The report then discusses the application of blockchain technology and its potential benefits and issues in addressing the issue of medical certificate forgery. The focus of the project is on scalability and security, and the report explores the centralization vs decentralization issue, ultimately deciding on a decentralized approach using encryption for security and IPFS for scalability. The project uses Solidity smart contracts to store medical certificate data on the blockchain, ensuring that the certificates are tamper-proof and immutable. Overall, this report provides a comprehensive overview of the issue of medical certificate forgery and the potential of blockchain technology to address this issue. The project's emphasis on scalability and security, and its use of decentralized technologies such as IPFS and encryption, makes it a promising solution for the medical industry's ongoing struggle with certificate forgery.